In the belly of the beast: How dietary changes and preexisting invasive prey may have promoted the success of a novel invasive amphibian - Maya J. Williams; Julia L. Riley; James Baxter-Gilbert (PLoS ONE, 2026)
Biological invasions provide unique opportunities to examine how populations cope with rapid ecological change, as well as the influence of human activity on our natural world. The island of Newfoundland, Canada, has no native amphibians; however, five species have established non-native populations, including one caudatan, the Eastern Red-backed Salamander ( Plethodon cinereus ). We posit that this salamander’s successful colonisation may have been mediated by dietary shifts that allowed them to capitalize on a greater variety of prey, as well as by exploiting pre-existing invasive prey communities – both these mechanisms could limit the likelihood of competitive exclusion and promote establishment in a novel environment. To examine this, we identified stomach contents of Newfoundland Eastern Red-backed salamanders, characterised the prey as native or invasive, and compared the dietary composition of the invasive population to that of conspecifics in the native range through a systematic literature review. As predicted, the invasive salamander population’s diet is more generalised (i.e., a broader dietary niche) than the native salamanders, and invasive invertebrates comprised two thirds of the volume of prey eaten by invasive salamanders. Our research provides insight into the Niche Breadth Invasion Hypothesis as well as the Invasional Meltdown Hypothesis, which are mechanisms that may have allowed this species to establish a population in an island ecosystem. Furthermore, our research suggests that prior invasions of a diverse invertebrate community to Newfoundland may have bolstered the invasive potential of this novel, non-native salamander.